2022
DOI: 10.1111/papr.13181
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of BurstDR™ spinal cord stimulation for non‐operated discogenic low back pain

Abstract: Introduction Chronic discogenic low back pain (CD‐LBP) is caused by degeneration of the disc due to trauma to the annulus or by unprovoked degeneration, resulting in chronic pain. Spinal cord stimulation (SCS) employing the BurstDR™ waveform has been shown to be an effective treatment in a variety of chronic pain conditions. The aim of this prospective case study was to determine the effect of BurstDR™ SCS on pain relief, disability, and patient satisfaction in a population with CD‐LBP. Methods Seventeen subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Furthermore, a prospective study conducted by Mons MR et al found that the BurstDR™ Spinal Cord Stimulation in non-operated discogenic low back pain disease resulted in a significant reduction in back pain, leg pain, and quality of life in patients, decreasing the level of disability rated in ODI and quality of life, which persisted during the 12 months of the study [23]. It is an important observation that cannot be compared to our group, as we qualified for SCS only the patients who had their spine operated on before.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, a prospective study conducted by Mons MR et al found that the BurstDR™ Spinal Cord Stimulation in non-operated discogenic low back pain disease resulted in a significant reduction in back pain, leg pain, and quality of life in patients, decreasing the level of disability rated in ODI and quality of life, which persisted during the 12 months of the study [23]. It is an important observation that cannot be compared to our group, as we qualified for SCS only the patients who had their spine operated on before.…”
Section: Discussionmentioning
confidence: 97%
“…Chronic discogenic low back pain (CD‐LBP) is caused by disk degeneration that can happen as a result of a trauma to the disk. Mons et al 1 conduced an interesting prospective study on the use of Burst DR™ spinal cord stimulation for treating CD‐LBP. Investigators enrolled 17 patients, but only 15 patients had more than 50% improvement with trail and received the permanent implant.…”
mentioning
confidence: 99%